Fault-tolerant control of a permanent magnet synchronous motor based on hybrid control strategies using a multi-variable filter - Bahiddine, Miloud; Belhamra, Ali (Institute of Advanced Engineering and Science, 2024)
This paper describes direct torque control (DTC) of a permanent magnet synchronous machine (PMSM) powered by a two-level voltage inverter whose switching of switches is based on the space vector modulation (SVM). To enhance the robustness of control in the presence of faults, we have enhanced DTC with SVM by incorporating a multivariable filter to address fault current effects. In this modification, traditional proportionalintegral controllers are substituted with sliding mode controllers. This approach results in a revised structure known as DTC-SVM with sliding mode control, presenting a new fault-tolerant control diagram. A comparative study between these different control strategies is carried out. The simulation results show clearly the interest of a multi-variable filter association with the DTC-SVM-sliding mode control2 (SMC2) in degraded mode. The outcomes achieved provide substantial evidence supporting the resilience and efficacy of this approach, especially when confronted with the influence of the faults current.